1980
DOI: 10.1172/jci109956
|View full text |Cite
|
Sign up to set email alerts
|

A-IMilano apoprotein. Decreased high density lipoprotein cholesterol levels with significant lipoprotein modifications and without clinical atherosclerosis in an Italian family.

Abstract: A B S T R A C T Significant hypertriglyceridemia with a very marked decrease of high density lipoproteins (HDL)-cholesterol levels (7)(8)(9)(10)(11)(12)(13)(14) proteins provided evidence for multiple isoproteins in the apoprotein(apo)-A-I range, with nine different bands being detected instead of the usual four bands observed in normal subjects. Two-dimensional immunoelectrophoresis against apo-A antiserum indicated a clear reduction of apo-A in the alpha electrophoretic region, with splitting of the protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
184
0
3

Year Published

1984
1984
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 437 publications
(188 citation statements)
references
References 39 publications
1
184
0
3
Order By: Relevance
“…36 The carriers of this mutation have markedly reduced HDL cholesterol levels and a high prevalence of hypertriglyceridemia without an increased incidence of vascular disease. 24 The longer half-life of apoA-I Milano compared with the wild type may, at least in part, explain the former's possible favorable effect. 37 We have previously shown that apoA-I Milano inhibits the formation of intimal lesions after balloon injury of the aorta in hypercholesterolemic rabbits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…36 The carriers of this mutation have markedly reduced HDL cholesterol levels and a high prevalence of hypertriglyceridemia without an increased incidence of vascular disease. 24 The longer half-life of apoA-I Milano compared with the wild type may, at least in part, explain the former's possible favorable effect. 37 We have previously shown that apoA-I Milano inhibits the formation of intimal lesions after balloon injury of the aorta in hypercholesterolemic rabbits.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of purified human apoA-I reconstituted in phospholipid liposomes was compared with that of liposomes containing recombinant apoA-I Milano , a mutant form of apoA-I believed to have increased antiatherogenic capacity. 24 …”
mentioning
confidence: 99%
“…Patients heterozygous for the Lys107 f 0 mutation (apoA-I Helsinki ) (20) have a 30% reduction in apoA-I and approximately 40% reduction in PON plasma concentration (19), and some subjects have documented coronary disease. Carriers of the apoA-I Milano trait characterized by the presence of a sulfhydryl group in apoA-I (Arg173 f Cys mutation) (21) have substantial reductions in apoA-I (approximately 50%) but have no predisposition for CAD. These patients have PON mass and activity similar to normal subjects (19).…”
mentioning
confidence: 99%
“…Moreover, both genetic studies and clinical trials support the idea that, in some circumstances, HDL-C levels may behave opposite to what is predicted by the Framingham assessment model (9,10). For example, carriers of the apoAI Milano mutation present with low levels of HDL-C but are resistant to atherosclerosis (11,12), whereas subjects with cholesteryl ester transfer protein (CETP) deficiency have high HDL-C levels but are not patently protected against atherosclerosis (13)(14)(15)(16). In addition, common polymorphisms in the CETP and hepatic lipase genes linked to elevated HDL-C levels are associated with increased cardiovascular events (17,18).…”
Section: Hdl Functionmentioning
confidence: 97%